Outcome of renal transplantation in small infants: a match-controlled analysis - Weitz, Marcus; Krupka, Kai; Tönshoff, Burkhard (Pediatric nephrology, 2018)
BACKGROUND: Infants with a body weight of less than 10 kg are often not considered to be suitable candidates for renal transplantation (RTx). The objective of this study was to evaluate this arbitrary weight threshold for pediatric RTx. - METHODS: We conducted a multicenter, retrospective, match-controlled cohort study on infants weighing less than 10 kg at time of engrafting (low-weight group [LWG], n = 38) compared to a matched control group (n = 76) with a body weight of 10-15 kg, using data from the first 2 years post-transplant derived from the CERTAIN Registry. - RESULTS: Patient survival was 97 and 100% in the LWG and control groups, respectively (P = 0.33), and death-censored graft survival was 100 and 95% in the LWG and control groups, respectively (P = 0.30). Estimated glomerular filtration rate at 2 years post-transplant was excellent and comparable between the groups (LWG 77.6 ± 34.9 mL/min/1.73 m2; control 74.8 ± 29.1 mL/min/1.73 m2; P = 0.68). The overall incidences of surgery-related complications (LWG 11%, control 23%; P = 0.12) and medical outcome measures (LWG 23%, control 36%, P = 0.17) were not significantly different between the groups. The medical outcome measures included transplant-related viral diseases (LWG 10%, control 21%; P = 0.20), acute rejection episodes (LWG 14%, control 29%; P = 0.092), malignancies (LWG 3%, control 0%; P = 0.33) and arterial hypertension (LWG 73%, control 67%; P = 0.57). - CONCLUSIONS: These data suggest that RTx in low-weight children is a feasible option, at least in selected centers with appropriate surgical and medical expertise.
Gesehen am 04.07.2019